Do local banks credits to private sector and domestic direct investments affect FDI inflow? (Malaysia evidence) - Nezakati, Hossein; Fakhreddin, Farzad; Vaighan, Behzad Mahmoudi (IDOSI Publications, 2011)
This study analysis the factors affecting foreign direct investment inflow in manufacturing sector in Malaysia in between 1974 to 2009, mainly focused on two determinants; domestic credit to private sector by local commercial banks and domestic direct investment. Growth Domestic product and the Trade Openness are also included in the model respectively; the results indicate that Gross Domestic Product of manufacturing, Trade openness, domestic credit to private sector and domestic direct investment significantly influenced the level of foreign direct investment inflow into Malaysia. This study manipulate the cointegration test method and Vector Auto Regression Granger causality between logarithm of foreign direct investment, domestic credit to private sector and domestic direct investment respectively which illustrates both variables are cointegrated and also Granger caused of foreign direct investment.